Evaluation of methane mitigation by organic feed additives in dual-flow continuous culture - B.A. Wenner; G. Praisler; K. Mitchell; J. Velez; P.S. Yoder (JDS Communications)
Sustainability is interwoven with consumer expectations of organic production systems, yet there are few nutritional options for organic dairy systems to approach methane (CH4) mitigation. The objective of the current study was to compare 3 feed additives for CH4 mitigation. We hypothesized that each additive would decrease CH4 production in continuous culture when compared with a control diet. Using dual-flow continuous culture fermenters fitted for CH4 and hydrogen (H2) sampling, 4 treatments were arranged in a 4 × 4 Latin square design. Treatments were a negative control (CON, 60:40 concentrate:orchardgrass pellet mix, 17.1% CP, 33.0% NDF, 20.1% ADF, and 27.1% starch) fed twice daily a total 80 g/d DM (CON) and comparing one of the 3 additives: kelp powder (KP) at 1.7 g/d, essential oils (EO) at 3 mg/d, or pistachio-based biochar (BC) at 1.6 g/d. All dosages were calculated based on previous data and supplier recommendations scaled to dual-flow continuous culture functional volume. Experimental periods included 7 d of adaptation and 4 d of sampling (11 d total), and buffer and solids dilution rates were maintained at 7%/h and 5%/h, respectively. The main statistical model included fixed effect of treatment and random effects of fermenter and period. Gas production data were measured by feeding; thus, analysis included a repeated effect of feeding and hourly VFA samples a repeated effect of hour. Only EO decreased CH4 production compared with CON (43.1 vs. 47.4 mmol/feeding, SD: 3.96). There was no effect of treatment on H2 emission, nor H2 or CH4 in the aqueous phase. There was also no effect of treatment on nutrient digestibility despite large numerical differences in fiber digestibility, nor the production of primary VFA. However, KP decreased production of isobutyrate and isovalerate compared with CON. While the present data illustrate efficacy of an essential oil product to decrease CH4 emission, decreases in CH4 were not supported by statistically significant gains in VFA that could translate to increased milk production in the dairy cow.